Exploring Antioxidant and Anti-diabetic Activities, and Chemical Contents of Extracts from Thai Traditional Medicine (Pra-Sa-Ka-Phrao Remedies) and Its Plant Ingredients - Ninlaor, Theeraphong; Itharat, Arunporn; Ruangnoo, Srisopa; Choockong, Chadchom; Naknarin, Suchada; Davies, Neal M. (Asian Medical Journal and Alternative Medicine, 2024)
Introduction: Pra-Sa-Ka-Phrao complete (PSKPC) remedy is a Thai traditional medicine published in the Thailand National List of Essential Medicines (NLEM). In this research, we have developed a modified version of the remedy, named as Pra-Sa-Ka-Phrao incomplete (PSKPIC), following the FDA Thailand’s guidelines for using it as a food supplement. Notably, there is a lack of studies concerning biological activities and chemical constituents of both remedies. Objectives: This study aimed to investigate and compare the antioxidant and anti-diabetic activities, and chemical contents derived from both remedies and its plant ingredient extracts. Methods: Extraction was performed by maceration in 95% ethanol and decoction. The antioxidant activity was investigated using a DPPH, ABTS, FRAP, and TBARS assays, while the anti-diabetic (α-amylase, α-glucosidase inhibitory activities) were also evaluated, along with the determination of total phenolic (TPC) and total flavonoid (TFC) contents. Results: The ethanolic extract of Zingiber officinale (ZOE) and water extract of Ocimum sanctum (OSW) exhibited the highest antioxidant activity, TPC, and TFC contents. The antioxidant results revealed that the PSKPIC water extract (PSKPICW) showed greater potency than PSKPC water extract in all assays. Additionally, the PSKPICW demonstrated higher TPC and TFC levels compared to the PSKPC remedy. Glycyrrhiza glabra (GGE) presented the strongest α-glucosidase inhibitory activity. However, all remedy extracts did not significantly affect anti-diabetic activity. Conclusions: These results show the efficacy of the PSKPICW remedy, used as food ingredients or food supplements extract, and selected active extracts, such as ZOE and OSW, which supports their use in antioxidant products.